Kewargaan Inklusif sebagai Paradigma Alternatif Pelayanan Publik - Wasisto Raharjo Jati (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2014)
This article traces to endeavor the concept of public services in the practice of inclusive citizenship. Contextualization of citizens should be important to be argued in order state eﬀ ort to fulﬁ lling its citizen basic needs. There are three major schools of public service regime; the liberal, social democratic, and social investment wherein each paradigm gives a diﬀ erent sense of the citizens. Liberal regime deﬁ nes citizen guaranteed to choose their public service patt ern, amidst state or market. Social democratic regime emphasizes obligatory state in terms of public services for its citizens. Meanwhile, the social investment act rationally in providing services to its citizens. The paradigm of Inclusive citizenship emerges as a form of alternative response of the third paradigm in providing public services and comprehensive democratic to every citizen. Implementation of inclusive citizenship toward public service reform is urging and signiﬁ cant to recommend how far and beyond state posited citizen as their client who must be served vice versa. This article will elaborate more on the meaning of inclusive citizenship in the public service.